Building a vision for more effective equity indices and planning tools - Rosan, Christina D.; Heckert, Megan; Zerbo, Russell; Benitez Mercado, Erykah (Frontiers in Sustainable Cities, 2022)
Recent years have seen a proliferation of equity indices and environmental justice screening tools to support environmental planning processes. While the equity index framework has proven important to advance the conversation around environmental equity and connect need to investments, we see opportunities to rethink and expand on the index model to address issues of climate justice and preparedness through the development of PREACT (Planning for Resilience and Equity through Accessible Community Technology), a multipurpose and multi-scalar climate preparedness and neighborhood planning software application informed by community need and community assets. Since our initial development of a GSI Equity Index, the conversation about GSI, equity, climate, urban heat, environmental justice, racial justice, and air pollution has changed at all scales of government and this necessitates a rethinking of the tool. Ultimately, we see it as important that these tools offer a much wider range of uses, particularly to be meaningful for community planning and advocacy.